2012
DOI: 10.1002/eji.201142240
|View full text |Cite
|
Sign up to set email alerts
|

The development of IL‐17/IFN‐γ‐double producing CTLs from Tc17 cells is driven by epigenetic suppression of Socs3 gene promoter

Abstract: The plasticity of T lymphocytes induced by epigenetic modifications of gene promoters may play a pivotal role in controlling their effector functions, which are sometimes causally associated with immune disorders. IL -17-producing T cells, which induce type 17 immune responses, are newly identified pathogenic effector cells. The type 1 signature cytokine IFN-γ strongly inhibits their differentiation, indicating a mutually exclusive relationship between type 17-and type 1-immune responses. However, many reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Notably, coexpression of both IL-17A and IFNg was observed early posttransplant, which appears to be a general feature of Tc17 cells. 15,32,34 This dual expression has been attributed to epigenetic suppression of the regulatory protein SOCS3, 32 whose absence in donor T cells we have shown to also result in polyfunctional T-cell responses and exacerbated GVHD. 44 In this study, we found that Socs3 gene expression was downregulated in CD8 Table 3).…”
Section: Yfpmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, coexpression of both IL-17A and IFNg was observed early posttransplant, which appears to be a general feature of Tc17 cells. 15,32,34 This dual expression has been attributed to epigenetic suppression of the regulatory protein SOCS3, 32 whose absence in donor T cells we have shown to also result in polyfunctional T-cell responses and exacerbated GVHD. 44 In this study, we found that Socs3 gene expression was downregulated in CD8 Table 3).…”
Section: Yfpmentioning
confidence: 71%
“…We have previously shown that in a murine model of allo-SCT, G-CSF mobilization promotes donor Th17/Tc17 differentiation and that IL-17A-deficient allografts protect recipients from CD8 1 T cellmediated sclerodermatous GVHD. 15 Recent studies in other disease 12,32,34,[39][40][41] ; however, plasticity studies of Tc17 have been limited to the use of in vitro polarized CD8 1 T cells. To circumvent this limitation, we used a murine IL-17A "fate-mapping" reporter model to characterize an inflammatory Tc17 lineage that develops during GVHD, and to our knowledge, we are the first to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine IL-12 has been shown to promote the switch of Tc17 toward Tc1 via epigenetic suppression of Socs3, which on the one hand promotes Tc17 generation (Satoh et al 2012;Yu et al 2013) and on the other dampens Tc1 effector development (Cui et al 2011). Interestingly, in allergic airway disease IFN-c-deficient CD8…”
Section: Similar To Cd4mentioning
confidence: 99%
“…[1][2][3][4][5][6] Plasticity has been widely reported in CD4 IL-17A 1 (Tc17) T cells in a range of infectious and autoimmune settings. [6][7][8][9][10][11][12] We have recently described Tc17 cytokine plasticity in murine allo-SCT recipients, 1 which is characteristic of a hyper-proinflammatory T-cell subset that contributes to GVHD but fails to mediate graft-versus-leukemia effects. 1,3 Th17 cells have been reported to transdifferentiate toward highly functional distinct phenotypes, including the acquisition of regulatory and follicular B-cell helper function (Tfh).…”
Section: Introductionmentioning
confidence: 99%